2014
DOI: 10.4238/2014.may.16.2
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine induces blood vessel global hypomethylation mediated by LOX-1

Abstract: ABSTRACT. Homocysteine (Hcy) is an independent risk factor of atherosclerosis through its involvement with the methionine cycle. In this study, we aimed to determine the blood vessel global methylation rate in Hcy-induced atherosclerosis in apolipoprotein-E-deficient (ApoE -/-) mice, and to explore the possible mechanism of this change in endothelial cells. ApoE -/-mice were divided into a hyperlipidemia (HLP) group, a hyperhomocysteinemia (HHcy) group, and an HHcy + folate + vitamin B12 (HHcy+FA+VB) group. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…In vitro experiments also showed that Hcy accelerated lipid accumulation in the foam cells. These results suggested that Hcy might promote the development of atherosclerosis as well as formation of the foam cells, which is in line with previously reported studies [4]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In vitro experiments also showed that Hcy accelerated lipid accumulation in the foam cells. These results suggested that Hcy might promote the development of atherosclerosis as well as formation of the foam cells, which is in line with previously reported studies [4]. …”
Section: Discussionsupporting
confidence: 93%
“…Apo E-/- mice fed with methionine was a typical method to replicate hyperhomocysteinemia animal model [5]. Folic acid and vitamin B12 interfered Hcy production of methionine cycle [4, 8]. Increased lesions were observed in the HHcy group compared to the HLP group; moreover, when compared to HHcy+FA+VB group, the HHcy group demonstrated increased lesions (Fig 1A and 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Folate had decreased hepatic SAH content but did not affect SAM content which resulted in higher SAM/SAH ratio. Reduced serum homocysteine and SAM had been previo u s l y o b s e r v e d i n h i g h -f a t d i e t -i n d u c e d hyperhomocysteinaemic ApoE −/− mice supplemented with folate and vitamin B 12 [47], while another study reported decreased plasma homocysteine but increased plasma SAM as well as SAM/SAH ratio in patients with hyperhomocysteinaemia [33]. Collectively, it can be said that folate increases methylation ratio, either by increasing SAM or decreasing SAH.…”
Section: Discussionmentioning
confidence: 97%
“…In the processes of methionine metabolism, there are several byproducts, including Hcy, SAM and SAH, and previous studies have demonstrated that alterations in the SAM/SAH ratio may be more directly associated with vascular damage, compared with Hcy or the other intermediates (31)(32)(33). A number of studies have described that increased levels of Hcy are always followed by higher concentrations of SAH, and it may be an important mediator of toxicity in the body.…”
Section: Discussionmentioning
confidence: 99%